FROM SATISFACTION TO LOYALTY: MODELING THE IMPACT OF TRAVEL AND DESTINATION EXPERIENCES ON REVISIT INTENTIONS - Bhenu Artha; Ascasaputra Aditya; Antonius Satria Hadi; Bahri Bahri; Utami Tunjung Sari5; Niken Permata Sari6; Cahya Purnama Asri (Journal of Development Economics and Digitalization, Tourism Economics, 2025)
Tourism has become an important industry over the last few decades, and its economic impact, including direct, indirect, and induced effects, has been enormous. The purpose of this study is to determine the relationship between travel satisfaction, destination satisfaction, and revisit intention. To accomplish the aims and objectives of the research, a theoretical literature assessment is carried out, and a conceptual framework for further investigation is provided. We present that Destination Satisfaction significantly and positively influences revisit intention, travel satisfaction significantly and positively influences revisit intention, travel satisfaction significantly and positively influences destination satisfaction, and destination satisfaction significantly mediates the positive relationship between travel satisfaction and revisit intention.